2022
DOI: 10.1177/10406387221078583
|View full text |Cite
|
Sign up to set email alerts
|

Bovine coronavirus in the lower respiratory tract of cattle with respiratory disease

Abstract: Bovine coronavirus (BCoV) is a known cause of enteric disease in cattle; however, its role in bovine respiratory disease (BRD) is poorly understood, with a dearth of evidence of the detection of the virus in respiratory tract lesions. We coupled histologic evaluation of tracheal and lower airway tissues from 104 calves with BRD in which BCoV was detected in the lungs via PCR followed by direct detection of BCoV by immunohistochemistry and an RNA in situ hybridization assay (ISH; RNAscope technology). RNAscope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Although BCoV is associated with enteric disease due to its dual tropism for the respiratory and digestive systems 61 , this virus was only amplified from the DNS of one calf that was simultaneously infected with OvGHV2 without being detected from the intestinal and fecal samples evaluated. Accordingly, these findings confirmed that BCoV was associated only with the development of the pulmonary distress syndrome herein described; similar results were previously described 31,58,60,62,63 .…”
Section: Discussionsupporting
confidence: 92%
“…Although BCoV is associated with enteric disease due to its dual tropism for the respiratory and digestive systems 61 , this virus was only amplified from the DNS of one calf that was simultaneously infected with OvGHV2 without being detected from the intestinal and fecal samples evaluated. Accordingly, these findings confirmed that BCoV was associated only with the development of the pulmonary distress syndrome herein described; similar results were previously described 31,58,60,62,63 .…”
Section: Discussionsupporting
confidence: 92%
“…Fresh tissue samples were collected at the time of euthanasia, placed in separate plastic bags, and shipped on ice to the Iowa State University Veterinary Diagnostic Laboratory (ISU VDL). Fresh tissues were processed and analyzed at the ISU VDL as previously described (24). RT-rt PCR primers used were specific for the S gene of BCoV.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is clear that high detection rates of the virus have been noted in cattle with respiratory disease, either alone or with other pathogens and the virus has caused pathology through inoculation and infection in other studies [5,16,18,19,25,26,28,30]. More specifically, further studies have demonstrated the presence of the virus in respiratory tracts with histological evidence of pathology [24]. In this study, immunohistochemistry and an RNA in situ hybridization assay were both used to identify the presence of BCoV in the lower respiratory tract (the focus on the trachea and lungs) of calves.…”
Section: A Respiratory Syndromementioning
confidence: 97%
“…The virus primarily affects the epithelial cells of the respiratory tract, with attenuation and necrosis seen in these cells microscopically. Most commonly, tracheitis is seen along with rhinitis and interstitial pneumonia [5,24]. The most common clinical signs seen are coughing and rhinitis which may display with nasal discharge (serous to mucopurulent), and this may be coupled with pyrexia and anorexia.…”
Section: A Respiratory Syndromementioning
confidence: 99%